Comparison between a Direct and an Indirect Method for Determining Plasminogen - Hedner, Ulla; Nilsson, Inga Marie (Thrombosis and Haemostasis, 1971)
A caseinolytic method for plasminogen determination using 30% ammonium sulphate to remove the inhibitors was compared with an immunochemical method in 44 apparently healthy individuals, 25 pregnant women in the third trimester, 24 patients with different liver diseases, 20 patients receiving thrombolytic therapy, 7 patients with septicemia and 9 foetuses obtained by induced legal abortion. The correlation found was strong and the regression line was found to pass near origo, indicating that the two methods measured, the same substance.Both methods gave high plasminogen values in pregnant women and low values in patients receiving thrombolytic therapy and in foetuses.